Toward Visibly Transparent Organic Photovoltaic Cells Based on a Near-Infrared Harvesting Bulk Heterojunction Blend - James Durrant (ACS Applied Materials & Interfaces, 2020)
Wavelength-selective harvesting by organic solar cells (OSCs) has attracted significant research attention due to the unique potential of these materials for smart photovoltaic window applications. Here, a visibly transparent OSC is demonstrated by utilizing both near-infrared (NIR)-absorbing polymer donor and nonfullerene acceptor (NFA) materials with narrow optical band gaps of less than 1.4 eV. Despite the substantial overlap in absorption spectra between the donor and acceptor, sufficient lowest unoccupied molecular orbital (LUMO) and highest occupied molecule orbital (HOMO) energy offsets for efficient charge separation with concurrent very low voltage losses yield a power conversion efficiency (PCE) of 9.13%. Moreover, with the introduction of an ultrathin Ag film (8 nm) as a transparent top electrode, semitransparent OSCs exhibit an excellent dual-side photovoltaic performance of 5.7 and 3.9% under bottom and top illumination, respectively, with high transmittance reaching 60% at wavelengths from 400 to 600 nm. This approach is expected to provide a new perspective in developing the highly efficient and transparent OSCs.